Extended Infusion of Dexmedetomidine to an Infant at Sixty Times the Intended Rate - Bryan A. Max; Keira P. Mason (Hindawi Limited, 2010)
Dexmedetomidine is an 𝛼2 adrenergic agonist which has recently been approved in the United States for procedural sedation in adults. This report describes an infant who inadvertently received an intravenous infusion of dexmedetomidine at a rate which was 60 times greater than intended. We describe the hemodynamic, respiratory, and sedative effects of this overdose.